Perceptual-cognitive training: The next piece of the puzzle - Loffing, F.; Hagemann, M.; Farrow, D. (Routledge handbook of talent identification and development in sport, 2017)
In this chapter, we will point to the key concepts and findings related to research on perceptual-cognitive training and discuss the potential relevance of such training for talent development. We will conclude with a discussion of open issues and research perspectives that may help better understand whether perceptual-cognitive skill training is an important piece to consider within the puzzling issue of talent development in sport.